A Minireview for Recent Development of Nanomaterial-Based Detection of Antibiotics - Jiafu Hong; Mengxing Su; Kunmeng Zhao; Yihui Zhou; Jingjing Wang; Shu-Feng Zhou; Xuexia Lin (Biosensors, 2023)
Antibiotics are considered a new type of organic pollutant. Antibiotic residues have become a global issue due to their harm to human health. As the use of antibiotics is increasing in human life, such as in medicine, crops, livestock, and even drinking water, the accurate analysis of antibiotics is very vital. In order to develop rapid and on-site approaches for the detection of antibiotics and the analysis of trace-level residual antibiotics, a high-sensitivity, simple, and portable solution is required. Meanwhile, the rapid nanotechnology development of a variety of nanomaterials has been achieved. In this review, nanomaterial-based techniques for antibiotic detection are discussed, and some reports that have employed combined nanomaterials with optical techniques or electrochemical techniques are highlighted.